ChemInform Abstract: Convenient Synthesis of New N‐3‐Substituted Pyrido[1′, 2′:1, 5]pyrazolo[3, 4‐d]pyrimidine‐2, 4(1H, 3H)‐dione Derivatives. Issue 7 (18th February 2014) - Belaroussi, Rabia; El Bouakher, Abderrahman; Marchivie, Mathieu; Massip, Stephane; Jarry, Christian; El Hakmaoui, Ahmed; Guillaumet, Gerald; Routier, Sylvain; Akssira, Mohamed
Abstract The synthesis of the title compounds (VII) is based on the condensation of 1‐aminopyridinium salt (I) with dimethyl acetylenedicarboxylate followed by regioselective saponification to give the key intermediate (IV) which can be converted to the useful tricyclic derivatives.